Population dynamics in Korogwe : demographic surveillance system (DSS) in Tanga Region, Tanzania - Kamugisha, Mathias Leo (Centre for Actuarial Research (CARE), 2015)
A demographic surveillance system (DSS) is commonly used to generate and handle longitudinal follow-up data relating to demographic and health related events in a specified area. In the Korogwe DSS site, information on vital events such as births, deaths and migration has been collected since the establishment of the site in 2005. The aim was to establish demographic and epidemiological indices so as to assist in the evaluation of health related interventions.